The challenge of banking services development – giving its rightful place to customer satisfaction - Moraru, Andreea-Daniela; Duhnea, Cristina; Mieilă, Mihai; Ghiță-Mitrescu, Silvia; Ilie, Margareta; Necula, Anda Ileana (Journal of Business Economics and Management, 2022)
Lately, the global banking services industry has faced numerous challenges: the digitalization, increased competition, the instability of monetary and foreign exchange markets, and the volatility of exchange rates. However, at present, banks are facing the greatest challenge of all that is, placing the customers at the centre of business and the systematic follow-up of customer satisfaction. The present paper aims at assessing the influence of a series of determinants and socio-demographic factors on customer satisfaction with banking services in Romania, using the probit and logit models. The research focused on the Romanian banking market due to its distinctiveness within the European context – performance indicators above the European average during the past five years and a concentration level that discloses a significant growth potential. The results of the two models employed revealed similar results, with the most influential variables on customer satisfaction being convenience, e-banking, quality, and revenues.First published online 14 March 2022